The Reaction of Household Consumption to Predictable Changes in Social Security Taxes - Parker, Jonathan A (American Economic Review, 1999)
The key implication of rational expectations and the basic life-cycle/permanent-income hypothesis: that predictable changes in income have no effect on the growth rate of consumption expenditures, is examined. This implication is important for understanding the effectiveness and optimal timing of fiscal policy, the causes and propagation of business cycles, and the effects of income fluctuations on the growth rate of the economy. Using household-level consumption data from the Consumer Expenditure Survey, whether expenditures on nondurable goods increase contemporaneously with predictable changes in Social Security tax withholding is tested. It is found that households do change their consumption expenditures in response to the predictable fluctuations in income induced by the Social Security tax system.